DAKWAH ISLAM MELALUI KOMUNIKASI SOSIAL - Wisri Wisri (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2013)
Islamic Da'wah, in essence, is not just to call or invite people to worship God by means of lectures, speeches and invites by force, but it’s scope is wider. Inviting people to kindness, mutual respect among human beings (creatures of God), love, protection and keeping the world peace are also parts of dakwah.The approach of Islamic da'wah is as a mission way to create a peaceful and secure society as well as to maintain harmony among human beings in the difference The view of the Koran on religious pluralism asserts that human diversity is not inevitable, a certain tradition to determine the common beliefs, values and traditions are necessary for social life Harmony is the goal of plural life. Harmony is a human relationship with other human beings in mutual respect, help, silaturrahim (visit), assistance, live peacefully side by side, greeting and so on, with the aim to strengthen human brotherhood.Plural society is a diverse community of various elements, layers, tribes, customs and beliefs. Besides, various issues will also arise from the plurality if it is not handled properly and wisely